Demonstrating molecule docking skills through e-module based on blended learning of a la carte model on higher education - Hanum Isfaeni; S. Supriyatin; Reza Mahardika; Mutiara Hasna Putri Suri; Sekar Darmastuti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Blended learning in higher education is evolving to be more personalized, diverse, innovative, student-centered, and high-quality. It presents an opportunity to redesign and enhance curricula. Higher education institutions are adopting a blended approach to complement traditional courses and enrich student learning experiences. However, research on students' molecular docking abilities in bioinformatics courses remains limited. This study examines implementing a blended learning à la carte model assisted by molecular docking e-modules to enhance students' molecular docking abilities. The research used a quasi-experimental method with a pre test-pot test design to assessing the effectiveness of the blended learning à la carte model assisted by e-modules to improving of the student molecular docking skills. Participants were 30 master's students in Biology Education at FMIPA UNJ. The effectiveness of the blended learning model assisted by e-modules was tested using an independent t-test. The results showed a significant difference, with a t-value of 9.21 (p = 0.001) at a confidence level of 0.01. These findings indicate that the à la carte blended learning model, supported by molecular docking e-modules, effectively enhances students' molecular docking skills in bioinformatics courses.